Blue fleck corneal iridescence: an occasional feature of Cogan's microcystic corneal dystrophy. Issue 12 (December 1983) - Dark, A. J.; Proctor, J.
Abstract : Flecks consisting of brilliant reflective blue dots and streaks were a prominent biomicroscopical feature in three patients with Cogan's microcystic corneal dystrophy. Two patients required epithelial debridement. We used the material obtained to investigate their histology and ultrastructure. A subepithelial accumulation of basement membrane-like material composed of ultrastructurally fine granules was deposited in alternating layers of compaction and rarefaction. The layers lie mostly parallel to the anterior corneal surface, but in some places they are folded. Such foldings are possibly the sites of multilaminar reflection and constructive interference, giving rise to the blue iridescence.